Advances in Synthesis and Functional Modification of Nanohydroxyapatite. (1st April 2018) - Dou, Linbo; Zhang, Yancong; Sun, Hanwen
Abstract : Nanohydroxyapatite material has been used to substitute for bone repair materials in clinical therapy in recent years. However, its osteogenesis effects are different due to its morphology, size, calcium phosphate ratio, crystallinity, and other differences. Thus, synthesis methods are continuously being improved to obtain synthetic materials similar to the nanohydroxyapatite in natural bone tissues in terms of biocompatibility and biological activity. Many synthesis methods are available for nanohydroxyapatite, and, among them, biological template biomimetic synthesis is the optimal method for obtaining highly bioactive and biocompatible nanohydroxyapatite, achieved by manipulating the morphology and physical and chemical properties, such as size, calcium phosphorus ratio, and degree of crystallinity. This article reviews the synthesis and functional modification of nanohydroxyapatite.